DISAIN PENGENDALI SLIP PADA HAUL TRUCK MENGUNAKAN METODE SLIDING MODE CONTROLLER - Ahmad Faizal (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2014)
Changes in road conditions and friction wheel slip can result in the vehicle causing inconvenience to the user of the vehicle. To overcome this it is necessary to control the vehicle to slip in a state of minimal slip. In this study developed a method of control of the Direct Torque Control (DTC) in the three-phase induction motor is used as a vehicle to haul truck. By looking at the methods of the selected settings existing sliding mode method to overcome the problem of slip that occurs on the vehicle. DTC method is used to set the torque value directly, while the sliding mode method is used to regulate and minimize slippage that occurs in the vehicle. Simulations conducted in this research. The results of the simulation study shows that the method of sliding mode controller can minimize the slip according to setpoin 0.2. Slip the resulting values ??are in the range of provisions that slip occurs in a vehicle with a value of ? = 0 to ? = 1.